Hypovigilance warning system: A review on driver alerting techniques - Arun, S.; Murugappan, M.; Sundaraj, Kenneth, Prof. Dr. (Institute of Electrical and Electronics Engineers (IEEE), 2011)
Link to publisher's homepage at http://ieeexplore.ieee.org/